Vozes do silêncio: variações da clínica - Mirim, Liz Andréa Lima (2011)
It was from a silent session that this work started. How to treat a patient who doesn t tell her story? After some time, she begins to write me letters, and it is with their help that the analysis comes into course. Is this silence a form of resistance, or does it speak, or tell me of my patient s life? In a different instance, I m to manage a workshop with women who refuse to make up a group. What does that refusal tell me? The troubles of this mismatch are to serve as the basic blocks for me to work on. Reflect on these experiences resistance, communication, gestures, sharing is the object of this work, along with the procedures adopted to make it possible to analyze that patient and to have those women participating in the workshop. What I try to understand are the voices of these silences. Silence is golden, reminds S. Ferenczi in the title of an article. I wonder why the author compares silence to so a noble and covetable material! From the concepts of Winnicott of therapeutic consults and psychoanalysis on demand, and of Fábio Herrmann of extensive clinics, I got willing to work on these two cases. So, what I long for in this work is to look at these two experiences and try to grasp what there is in them as therapeutic, how to harbor all the suffering they represented and to extract some sense from them, making the therapy moving on. Using the playing concept forged by Winnicott, we have here two examples of how the analyst may place him/herself in this game, each one drawing a scribble and offering it to the other to be completed